Trends of tuberculosis prevalence, treatment and prevention efforts - Ahmed, Ferdous Ara; Mkpa, Beatrice Onyinyechi; Afroz, Sadia; Naimul Islam Nakib, M.; Islam, Mussa Tasmiah (International Journal of Research in Medical Sciences, 2024)
Background: Tuberculosis (TB) remains a critical public health challenge in Dhaka, Bangladesh, characterized by significant prevalence, treatment, and prevention complexities. This study aims to investigate the trends of TB prevalence, treatment efficacy, and prevention efforts in a cohort of 300 TB cases in Dhaka. Methods: A cross-sectional study design was utilized to assess TB prevalence, treatment outcomes, and prevention efforts among 300 TB cases in Dhaka. Data was collected from medical records, patient interviews, and health facility reports between 2021 and 2023. Results: Our findings indicate a high prevalence of TB, with an increasing incidence of multi-drug-resistant TB (MDR-TB) among the studied population. The standard treatment regimen’s success rate was observed at 78%, with MDR-TB cases showing significantly lower success rates. Despite the widespread use of the Bacillus Calmette-Guérin (BCG) vaccine, the adult population remains vulnerable, highlighting the need for improved vaccination strategies. Prevention efforts, including public health interventions and contact tracing, were evaluated, revealing gaps in early diagnosis and patient follow-up. The study underscores the critical need for enhanced TB control programs, better diagnostic tools, and more effective treatment regimens. Addressing these challenges through targeted interventions and increased funding is essential to mitigate TB’s impact in Dhaka. Conclusions: Our research provides valuable insights into the current state of TB in Dhaka, advocating for strengthened efforts in combating this enduring public health threat.